A Systematic Literature Review of Process Mining Adoption: Insights from Technology, Organization, Process, and Trust Dimensions - Dias, Rawiro; Prabowo, Harjanto; Haryanto, Soepono; Isa, Sani Muhammad (Proceeding of International Conference on Informatics, Engineering, Science & Technology, 2025)
Process mining adoption has received growing academic attention in recent years. This study presents the literature on process mining adoption. We divided the 34 papers found into four dimensions: Technology, Organization, Process, and Value/Trust. Based on the analysis of the findings, the implementation of process mining is not only a technical issue, but also requires organizational readiness, contextualization of the process, and mechanisms to build process awareness and trust in the results. Existing and cutting-edge technologies can expand the potential of process mining, such as ERP, AI, and Robotic Process Automation (RPA). Organizational factors and user trust play a crucial role in ensuring continued adoption. These findings are expected to provide a series of research directions for government organizations.